Amphotropic Murine Leukemia Virus Entry Is Determined by Specific Combinations of Residues from Receptor Loops 2 and 4 - Lundorf, Mikkel D. (American Society for Microbiology, 1999)
Pit2 is the human receptor for amphotropic murine leukemia virus (A-MuLV); the related human protein Pit1 does not support A-MuLV entry. Interestingly, chimeric proteins in which either the N-terminal or the C-terminal part of Pit2 was replaced by the Pit1 sequence all retained A-MuLV receptor function. A possible interpretation of these observations is that Pit1 harbors sequences which can specify A-MuLV receptor function when presented in a protein context other than Pit1, e.g., in Pit1-Pit2 hybrids. We reasoned that such Pit1 sequences might be identified if presented in the Neurospora crassa protein Pho-4. This protein is distantly related to Pit1 and Pit2, predicted to have a similar membrane topology with five extracellular loops, and does not support A-MuLV entry. We show here that introduction of the Pit1-specific loop 2 sequence conferred A-MuLV receptor function upon Pho-4. Therefore, we conclude that (i) a functional A-MuLV receptor can be constructed by combining sequences from two proteins each lacking A-MuLV receptor function and that (ii) a Pit1 sequence can specify A-MuLV receptor function when presented in another protein context than that provided by Pit1 itself. Previous results indicated a role of loop 4 residues in A-MuLV entry, and the presence of a Pit2-specific loop 4 sequence was found here to confer A-MuLV receptor function upon Pho-4. Moreover, the introduction of a Pit1-specific loop 4 sequence, but not of a Pit2-specific loop 4 sequence, abolished the A-MuLV receptor function of a Pho-4 chimera harboring the Pit1-specific loop 2 sequence. Together, these data suggest that residues in both loop 2 and loop 4 play a role in A-MuLV receptor function. A-MuLV is, however, not dependent on the specific Pit2 loop 2 and Pit2 loop 4 sequences for entry; rather, the role played by loops 2 and 4 in A-MuLV entry can be fulfilled by several different combinations of loop 2 and loop 4 sequences. We predict that the residues in loops 2 and 4, identified in this study as specifying A-MuLV receptor function, are to be found among those not conserved among Pho-4, Pit1, and Pit2.